ACTUALIZATION OF MUPUK KEMBANG RITUAL IN CONSERVATION OF LOCAL RICE VARIETIES AND FOOD SOVEREIGNTY IN AREA OF WORLD CULTURAL LANDSCAPE CATUR ANGGA PURA BATUKARU, BALI - Wardi, I Nyoman (E-Journal of Cultural Studies, 2017)
Since the emergence of the green revolution in Bali around the 1970s to the present day, in a gradation way emerged a variety of environmental changes and subak culture which is quite apprehensive. Among other things, the destruction of genetic resources, especially local rice varieties, and the emergence of concerns about the possible extinction of local rice varieties. This article aims to explore the meaning of wisdom of mupuk kembang ritual in World Cultural Landscape Catur Angga Batukaru, in the context of conservation of local rice varieties and food sovereignty in Tabanan-Bali. The research was conducted through data collection with observation, in-depth interview, focus group discussion, and literature study. The collected data were analyzed in a descriptive-qualitative manner. The result of the study showed that mupuk kembang ritual usually is held towards the end of the pujawali ceremony on the cultural heritage of Catur Angga Pura Batukaru (Pura Muncaksari, Tambawaras, Besikalung, Pucak Petali, and Pura Batukaru) in Penebel District of Tabanan Regency. The mupuk kembang ritual is performed in the early morning (dawn), at around 04.00 - 06.00, where the holy man (pemangku) in trans condition (kerawuhan) put rice (Sri-Sedhana) rice (manik galih) to his people (bhakta) present in the pujawali ritual. Implicitly the ritual hinted rice (Oryza sativa) as a sacred plant or tree of life (kalpataru) and so that villagers, especially farmers (subak), conserve it, especially local rice varieties to be developed as the main source of life. The mupuk kembang ritual also supports government’s development programs in the context of maintaining food sovereignty in Bali.